AKTIVITAS ANTIOKSIDAN EKSTRAK Andrographis paniculata (Burm.f.) Ness DENGAN DUA PERBEDAAN PENGUAPAN - Rais, Ichwan Ridwan (Universitas Ahmad Dahlan, 2016)
Andrographis paniculata (Burm.f.) Ness is one of the native tradisional medicine in Indonesia which contain active flavonoid. It has potential activity as antioxidant, antibacterial, and inflammation. Antioxidant sensitive to light and heat. Flavonoid antioxidant activity could be decline by heat and oxidation. We can find these caution while evaporate the liquid solvent with heating in conventional evaporation to get dry extract. One of the conventional evaporation instrument is Rotary Evaporator. Other evaporation system, lyophillization is alternative to evaporate solvent without heat. This system uses instrument called Freeze Dryer. Present study about antioxidant activity influenced by two different evaporation using IC50 determination in DPPH oxidation proved that evaporation difference could change antioxidant ability. The result shows freeze dryer evaporation result with 17.06% of extract yield and 585.730 Âµg/mL IC50 value better than rotary evaporator with 24.96% of extract yield and 792.196 Âµg/mL IC50 value in solvent evaporate ability and antioxidant activity.